New co-products from an endangered tree species: Araucaria angustifolia (bertol.) kuntze - Sequin, Christian Javier (2024)
Araucaria angustifolia is a notable tree species distributed in the Atlantic forest of central-eastern South America. It has been considered acritically endangered species. Due to competition from other land uses, including agriculture and Pinus plantations, A. angustifolia has lostdistribution and plantation area. This study aims to investigate new co-products of A. angustifolia waste products that can be used to preventagricultural diseases. Brown spot is the most common foliar disease of soybeans and is caused by Septoria glycines. In this work, we evaluated theantifungal activity of plant tissue-derived compounds against S. glycines. The ethyl acetate extract of A. angustifolia leaves showed antifungalactivity and was analyzed by HPLC-PDA and GC-MS. The results show two compounds as the principal constituents of antifungal activity. Bothcompounds showed a base peak at m/z 79.08, but they could not be identified by comparison with GC-MS spectral libraries. However, peaks atm/z 91 and 119 indicate that both compounds may contain aromatic structures. As a result of this study, we found that A. angustifolia can be usedto obtain reliable antifungal compounds against S. glycines.